SISTEM INFORMASI PERHITUNGAN NILAI PERSEDIAAN BAHAN BANGUNAN DENGAN METODE RATA-RATA BERGERAK PADA TOKO BANGUNAN SENLI - Wira Cristina; Liza Safitri; Danandjaya Saputra (LPPM STMIK BANDUNG, 2020)
Adequate accounting system can be a tool for management in providing information fast, precise, and reliable. To reduce and overcome the fraud that occurs that can harm the company, then in the implementation of inventory activities need an adequate internal control. Sufficient internal control is expected to assist the leadership in maintaining the security of corporate wealth, preventing and finding fault and fraud that can harm the company. Software used as a tool in designing this system is NETBEAN 8.0 and MYSQL as a database. The methodology used for the development of this application is the waterfall method. The author performs the old system analysis and system analysis needs of the user to design this system. Senli is a store that sells building materials, that why merchandise inventory is very instrumental in supporting the trade. Therefore, the entrepreneur or trader must be able to manage his business well. Companies that can manage inventory, planning and controls well, will greatly help the community or consumers in meeting their needs. This planning activity isn’t a easy task, because in the planning must be determined the right amount, merchandise to be sold must be in accordance with the tastes of consumers and must be provided in a correct time.